2017
DOI: 10.1016/j.psychres.2017.09.063
|View full text |Cite
|
Sign up to set email alerts
|

The Stigma Resistance Scale: A multi-sample validation of a new instrument to assess mental illness stigma resistance

Abstract: Although associated with key recovery outcomes, stigma resistance remains under-studied largely due to limitations of existing measures. This study developed and validated a new measure of stigma resistance. Preliminary items, derived from qualitative interviews of people with lived experience, were pilot tested online with people self-reporting a mental illness diagnosis (n = 489). Best performing items were selected, and the refined measure was administered to an independent sample of people with mental illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…stigma resistance have been published in recent years (e.g., see Firmin et al, 2017); future research would benefit from using these instead of the Stigma Resistance subscale on the ISMIS, which displays consistently low internal consistency (Boyd et al, 2014). Alternatively, if our finding does not represent a type II error, results may suggest that the ability to resist stigma is relatively independent of metacognitive capabilities in those with PTSD.…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…stigma resistance have been published in recent years (e.g., see Firmin et al, 2017); future research would benefit from using these instead of the Stigma Resistance subscale on the ISMIS, which displays consistently low internal consistency (Boyd et al, 2014). Alternatively, if our finding does not represent a type II error, results may suggest that the ability to resist stigma is relatively independent of metacognitive capabilities in those with PTSD.…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…It is a continuous and active process of using one's experiences, skills, and knowledge to develop an optimistic identity toward mental illness. Theoretical work on SR suggests that resisting stigma has an important role in fighting internalized stigma, facilitating the recovery from psychiatric illness, adherence, promoting their self-esteem, empowerment, quality of life, functionality, and community reengagement [ 7 , 9 , 26 , 27 ]. In previous studies, cut-off point at 2.5 and above on the mean item score of the SR subscale was used to define moderate to high (referred to as “high”) stigma resistance and less than 2.5 for low stigma resistance [ 9 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the factor analysis showed that a three‐factor model demonstrated a more acceptable fit with the Chinese data, different from the original scale of five factors (Firmin et al, 2017). Of note, the original scale was developed from a conceptual model of stigma resistance concerning (1) personal stigma resistance, (2) peer stigma resistance, and (3) public stigma resistance (Firmin et al, 2017).…”
Section: Discussionmentioning
confidence: 79%
“…The SRS was developed in 2017 to assess multiple domains of stigma resistance (Firmin et al, 2017). It is a 20‐item scale with five factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation